Host invasion during rice-blast disease requires carnitine-dependent transport of peroxisomal acetyl-CoA - Ramos-Pamplona, Marilou; Naqvi, Naweed I. (Wiley, 2006)
In lower eukaryotes, beta‐oxidation of fatty acids is restricted primarily to the peroxisomes and the resultant acetyl‐CoA molecules (and the chain‐shortened fatty acids) are transported via the cytosol into the mitochondria for further breakdown and usage. Using a loss‐of‐function mutation in the Magnaporthe grisea PEROXIN6 orthologue, we define an essential role for peroxisomal acetyl‐CoA during the host invasion step of the rice‐blast disease. We show that an Mgpex6Δ strain lacks functional peroxisomes and is incapable of β‐oxidation of long‐chain fatty acids. The Mgpex6Δ mutant lacked appressorial melanin and host penetration, and was completely non‐pathogenic. We further show that a peroxisome‐associated carnitine acetyl‐transferase (Crat1) activity is essential for such appressorial function in Magnaporthe. CRAT1‐minus appressoria showed reduced melanization, but were surprisingly incapable of elaborating penetration pegs or infection hyphae. Exogenous addition of excess glucose during infection stage caused partial remediation of the pathogenicity defects in the crat1Δ strain. Moreover, Mgpex6Δ and crat1Δ mycelia showed increased sensitivity to Calcofluor white, suggesting that weakened cell wall biosynthesis in a glucose‐deficient environment leads to appressorial dysfunction in these mutants. Interestingly, CRAT1 was itself essential for growth on acetate and long‐chain fatty acids. Thus, carnitine‐dependent metabolic activities associated with the peroxisomes, cooperatively facilitate the appressorial function of host invasion during rice‐blast infections.